2018
DOI: 10.3390/ijms19082376
|View full text |Cite
|
Sign up to set email alerts
|

The ATR-Activation Domain of TopBP1 Is Required for the Suppression of Origin Firing during the S Phase

Abstract: The mammalian DNA replication program is controlled at two phases, the licensing of potential origins of DNA replication in early gap 1 (G1), and the selective firing of a subset of licenced origins in the synthesis (S) phase. Upon entry into the S phase, serine/threonine-protein kinase ATR (ATR) is required for successful completion of the DNA replication program by limiting unnecessary dormant origin activation. Equally important is its activator, DNA topoisomerase 2-binding protein 1 (TopBP1), which is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…ATR and CHK1 signaling could be initiated by TOPBP1 that is associated with CMG. In agreement with this hypothesis, the ATR-activating domain of TOPBP1 was recently found to play a role in origin suppression during the S phase (46). Recent findings by Saldivar et al (45) document ATR signaling suppressing CDK1 activity in the S phase and specifically at the S/G2 transition in unperturbed cells.…”
Section: Discussionsupporting
confidence: 59%
“…ATR and CHK1 signaling could be initiated by TOPBP1 that is associated with CMG. In agreement with this hypothesis, the ATR-activating domain of TOPBP1 was recently found to play a role in origin suppression during the S phase (46). Recent findings by Saldivar et al (45) document ATR signaling suppressing CDK1 activity in the S phase and specifically at the S/G2 transition in unperturbed cells.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, a recent study found that an ATR inhibitor not only induced unscheduled origin firing, but also revealed another mechanism of origin regulation through a Cdc7-dependent phosphorylation of GINS [ 128 ]. Finally, a very recent study found that the ATR-activation domain of TOPBP1 is required to suppress origin firing during the S phase [ 129 ], further supporting an important role for the ATR–Chk1 pathway in regulating the activation of origins.…”
Section: Regulation Of Dormant Origins: a Passive Or Active Mechanmentioning
confidence: 90%
“…In quiescent cells that underwent HS, 4% of the cells stayed at the S phase whereas HS-treated proliferating culture had 14% cells in the S phase. Most reports on ATR function link ATR to the important role during the S phase [4850]. Culture with low cell number in the S phase is more resistant to damage, and ATR expression is not required for DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%